Offloading methods on MEC networks using SDN technologies - Maia, João Pedro Almeida (2020)
As the 5th-Generation (5G) of mobile networks are starting to show up, new technologies are also emerging. Seeing that massive Internet of Things (IoT) is one of the main reasons for the creation of this new generation of mobile networks, since they require massive bandwidth and fast connections, these new technologies aim to leverage 5G networks and thus, improve network speeds as well as deliver services to a wider range of customers. IoT devices also lack the necessary computation resources to execute complex tasks, hence requiring to offload their tasks to more capable systems located at cloud datacenters. However, offloading to these datacenters may not be effective due to the communication delay. Multi-Access Edge Computing (MEC) environments can reduce this delay by relocating cloud resources closer to the end-users. By also applying Software Defined Networking (SDN) and Network Function Virtualization (NFV) techniques through the use of a controller and hosting services as Virtualized Network Functions (VNFs), they can redirect the traffic directed to the cloud datacenters to the local MEC server and provide faster services. In this thesis, a MEC architecture integrating an SDN controller and providing offloading services as VNFs was implemented. By using these offloading services along with a speed test application during tests, it proved to support fast response times. This thesis also presents a study on how containers and Virtual Machines (VMs) affect the network speed, by hosting the previous applications.